Radiation grafting graphene oxide reinforced polybenzimidazole membrane with a sandwich structure for high temperature proton exchange membrane fuel cells in anhydrous atmosphere. (June 2018) - Cai, Yangben; Yue, Zhouying; Teng, Xin; Xu, Shiai
Graphical abstract: The introduction of inorganic material and the sandwich structure can improve the combination properties of porous membrane effectively. Highlights: A three-layer membrane was prepared by the layer-by-layer method. The membrane has a high proton conductivity of 113.8 mS·cm −1 at 170 °C without humidity. The sandwich structure improves the mechanical properties and prevents the release of H3 PO4 . Abstract: A three-layer membrane (TLM) of radiation grafting graphene oxide reinforced polybenzimidazole/porous polybenzimidazole/radiation grafting graphene oxide reinforced polybenzimidazole (PBI-RGO/PPBI/PBI-RGO) was fabricated and then doped with phosphoric acid (PA) for high temperature proton exchange membranes (HT-PEMs) in anhydrous atmosphere. These TLMs have a sandwich structure and the diameter of most pores falls in the range between 500 nm and 2 μm. PA doped TLMs display excellent mechanical strength and oxidative stability. The tensile strength of PA doped PBI-RGO/PPBI/PBI-RGO membranes ranges from 22.7 to 38.5 MPa, which is significantly higher than that of PA doped PPBI membrane (7.9 MPa). The introduction of RGO and porous structure can improve the proton conductivity of membranes. The proton conductivity of PA doped PBI-RGO/PPBI-80/PBI-RGO membrane is 113.8 mS·cm −1 at 170 °C without humidity, with an increase of 4.9 times compared with that of PA doped PBI membrane. The sandwich structure endows the membrane with lower PA leakage and higher proton conductivity, thus making it a promising membrane for HT-PEM applications.